Intelliscan: developing an intelligent x-ray computed tomography scanning method - Wong, Rachel Xi Thung (Nanyang Technological University, 2024)
X-ray Computed Tomography (XCT) scanning is an exhaustive process, for each surface of an object to be sampled accurately, thousands of projections are needed. As the complexity of engineering components continues to grow, the demand for both time and computing power in obtaining a single XCT scan escalates significantly. This final year project aims to address this challenge by developing an algorithm designed to intelligently select the optimal object orientation before initiating an XCT scan. The primary objective is to streamline the scanning process, eliminating the need for acquiring thousands of projections for each scan while maximizing the quality of reconstructed surfaces in the XCT data. This report delves into the methodologies employed to obtain an optimal object orientation and the development of the algorithm. Through a detailed exploration of the process, the report illustrates the steps taken to refine the XCT scanning approach, significantly enhancing efficiency and data quality. The findings and insights presented herein contribute to the advancement of XCT technology, offering a novel perspective on optimizing object orientation for improved scanning outcomes.